الأسطول والقوة البحریة في سلطنة عُمان خلال النصف الأول من القرن التاسع عشر (Journal of the College of Education for Women, 2019)
Development and progress of the fleet and the navy in Oman duringthe reign of Sultan Said bin sultan from 1804 to 1856.It had second level in Arab Gulf and Indian Ocean during the first halfof nineteenth century. The fleet of Oman in this time became after Britishfleet.Several reasons were behind the development of Omani fleet- First : The aim of Sultan Said was to built a large navy yard in Arab Gulfand Indian Ocean to encourage him -to made many ships factories.- Second: Arab Gulf and Indian Ocean within the reign of Sultan Saidwittinsed the confilicts and wars between different forces it drived Sultan Saidto built agood and strong navy.- Third The main aim of Oman during the reign of Sultan Said was to protectthe trade of Oman and its trad relations.- Fourth: sultan said was desire to open some arias and he wanted to add manyparts to his country as happened as with Africa East (zangibar).Moreover this research consists of an introduction two sections andconclusion depending on different documents and sources in Arabic andEnglish.